2019
DOI: 10.3389/fphys.2019.00859
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary and Muscular Interactions: Potential Implications for Exercise (In)tolerance in Symptomatic Smokers Without Chronic Obstructive Pulmonary Disease

Abstract: Smoking and physical inactivity are important preventable causes of disability and early death worldwide. Reduced exercise tolerance has been described in smokers, even in those who do not fulfill the extant physiological criteria for chronic obstructive pulmonary disease (COPD) and are not particularly sedentary. In this context, it is widely accepted that exercise capacity depends on complex cardio-pulmonary interactions which support oxygen (O 2 ) delivery to muscle mitochondria. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 163 publications
(272 reference statements)
1
3
0
Order By: Relevance
“…Reduced maximal VE in smokers may be related to the chronic effects of smoking on pulmonary function. Our result was following previous studies demonstrating that VE was greater during heavy work [ 42 , 43 ]. Moreover, smokers had a higher VE for a given submaximal exercise intensity compared to non-smokers with a lower VO 2 leading to the elevation in VE/VO 2 .…”
Section: Discussionsupporting
confidence: 92%
“…Reduced maximal VE in smokers may be related to the chronic effects of smoking on pulmonary function. Our result was following previous studies demonstrating that VE was greater during heavy work [ 42 , 43 ]. Moreover, smokers had a higher VE for a given submaximal exercise intensity compared to non-smokers with a lower VO 2 leading to the elevation in VE/VO 2 .…”
Section: Discussionsupporting
confidence: 92%
“…According to Hawari et al (2013) , the acute harmful effects could be related to the reduced capacity for carrying oxygen due to the increase in carbon monoxide levels. The second hypothesis can be extrapolated from the effect of cigarette smoking on exercise capacity ( Muller et al, 2019 ). Muller et al (2019) identified abnormalities in the cardio-circulatory and respiratory chain, supporting oxygen delivery to muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis can be extrapolated from the effect of cigarette smoking on exercise capacity ( Muller et al, 2019 ). Muller et al (2019) identified abnormalities in the cardio-circulatory and respiratory chain, supporting oxygen delivery to muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced exercise capacity has shown in smoker older people compared with nonsmoker older people (24). The musclelung-heart axis may cause reduced exercise capacity in smokers (25,26). Physical activity and smoking are inversely related as physical activity and exercise can decrease inflammatory markers associated with decreased cardiovascular fitness (27).…”
Section: Discussionmentioning
confidence: 99%